Effects of a Need-Supportive Motor Skill Intervention on Children's Motor Skill Competence and Physical Activity - Joonyoung Lee; Tao Zhang; Tsz Lun (Alan); Xiangli Gu (MDPI AG, 2020)
A need-supportive environment can provide various motivational benefits to impact children’s psychomotor developmental levels. However, very little is known about the effects of need-supportive motor skill intervention on children’s motor skill competence and physical activity by gender. Guided by self-determination theory (SDT), this study aimed to (a) investigate the effect of a need-supportive fundamental movement skill (FMS) program on children’s FMS competence and moderate-to-vigorous physical activity (MVPA), and (b) explore potential gender differences in these effects. Thirty-six children (63.8% girls; Mage = 6.52 ± 0.97) participated and were divided into two groups: an intervention group (24 need-supportive FMS sessions over eight weeks) and a control group. A repeated-measures multivariate analysis of variance (MANOVA) was used to examine the influence of the motor skill intervention on FMS competence and MVPA over time by group (intervention, control) and gender (boys, girls). The results showed (a) significant group differences between the intervention and control group in FMS competence and MVPA (p < 0.001), (b) non-significant gender differences between boys and girls in FMS competence and MVPA (p = 0.85), and (c) non-significant interaction effects over time (p = 0.52). The findings highlight that a need-supportive FMS program may enhance FMS development and daily physical activity for both genders during the early school years.